(untitled) (Ciudades, 2017)
This text is a contribution to a reassessment of the role of the historical centre of Covilhã, a town seeking affirmation and whose recent expansion is remarkable. We do this by analyzing the material collected in interviews with local people, on individual and collective behalf, who have their representations strongly shaped by the wool-factory industries and by a traditional town planning which is typical of the upland morphology. The intertwining of the factory with the residential fabric has reached such a density that Covilhã was classified as “factory town” in contrast to a diffuse industrialization that has shaped many other regions of the country. This social and urban scenery is viewed in the context of an open reading of the concept of heritage towards its extension to areas deemed of heritage value, being now old-fashioned or about to be destroyed, and that are the hallmarks of the historical specificity of the urbanization of Covilhã.